Autoimmunity and antibody affinity maturation are modulated by genetic variants on mouse chromosome 12. (April 2015) - Collin, Roxanne; Dugas, Véronique; Chabot-Roy, Geneviève; Salem, David; Zahn, Astrid; Di Noia, Javier M.; Rauch, Joyce; Lesage, Sylvie
Abstract: Autoimmune diseases result from a break in immune tolerance leading to an attack on self-antigens. Autoantibody levels serve as a predictive tool for the early diagnosis of many autoimmune diseases, including type 1 diabetes. We find that a genetic locus on mouse chromosome 12 influences the affinity maturation of antibodies as well as autoantibody production. Thus, we generated a NOD. H2 k congenic strain bearing B10 alleles at the locus comprised within the D12Mit184 and D12Mit12 markers, which we named NOD. H2 k - Chr12 . We determined the biological relevance of the Chr12 locus on the autoimmune process using an antigen-specific TCR transgenic autoimmune mouse model. Specifically, the 3A9 TCR transgene, which recognizes a peptide from hen egg lysozyme (HEL) in the context of I-A k, and the HEL transgene, which is expressed under the rat-insulin promoter (iHEL), were bred into the NOD. H2 k - Chr12 congenic strain. In the resulting 3A9 TCR:iHEL NOD. H2 k - Chr12 mice, we observed a significant decrease in diabetes incidence as well as a decrease in both the quantity and affinity of HEL-specific IgG autoantibodies relative to 3A9 TCR:iHEL NOD. H2 k mice. Notably, the decrease in autoantibodies due to the Chr12 locus was not restricted to the TCR transgenic model, as it was also observed in the non-transgenic NOD. H2 k setting. Of importance, antibody affinity maturation upon immunization and re-challenge was also impeded in NOD. H2 k - Chr12 congenic mice relative to NOD. H2 k mice. Together, these results demonstrate that a genetic variant(s) present within the Chr12 locus plays a global role in modulating antibody affinity maturation. Highlights: Generation of NOD. H2 k - B10 chromosome 12 congenic mice. The chromosome 12 (Chr12) locus defines a new autoimmune susceptibility locus. The quantity and affinity of IgG autoantibodies are influenced by the Chr12 locus. The Chr12 locus reveals novel candidate genes for antibody affinity maturation.